2021
DOI: 10.3390/antiox10091394
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Modulation of the Mitochondrial Metabolism and Redox in Bone Homeostasis and Osteoporosis: How Biophysics Converts into Bioenergetics

Abstract: Bone-forming cells build mineralized microstructure and couple with bone-resorbing cells, harmonizing bone mineral acquisition, and remodeling to maintain bone mass homeostasis. Mitochondrial glycolysis and oxidative phosphorylation pathways together with ROS generation meet the energy requirement for bone-forming cell growth and differentiation, respectively. Moderate mechanical stimulations, such as weight loading, physical activity, ultrasound, vibration, and electromagnetic field stimulation, etc., are adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“…PGC-1α stimulates Sirtuin 3 activity on osteogenic differentiation ( Buccoliero et al, 2021 ). How different biophysical stimuli may affect mitochondrial metabolism bone was recently reviewed by ( Wang F.-S. et al, 2021 ). In rat skeletal muscle tissue, the expression of PGC-1α and HIF-1α were differently affected by the training regimen (continuous, moderate exercise vs high-intensity interval) ( Ahmadi et al, 2021 ).…”
Section: Oxidative Stress and Bone Mechanobiologymentioning
confidence: 99%
“…PGC-1α stimulates Sirtuin 3 activity on osteogenic differentiation ( Buccoliero et al, 2021 ). How different biophysical stimuli may affect mitochondrial metabolism bone was recently reviewed by ( Wang F.-S. et al, 2021 ). In rat skeletal muscle tissue, the expression of PGC-1α and HIF-1α were differently affected by the training regimen (continuous, moderate exercise vs high-intensity interval) ( Ahmadi et al, 2021 ).…”
Section: Oxidative Stress and Bone Mechanobiologymentioning
confidence: 99%
“…DEGs in the Aβ 25−35 /EGCG group were mainly enriched in cell translation, extracellular matrix, wound healing, cytoplasm, and growth factor stimulation (Figure 7B Analysis of the synergistic mechanism of EGCG and L-theanine from the transcriptome level. (1)(2)(3)(4) The results showed that the cluster map of DEGs in the Aβ25-35-vs-Aβ25-35/EGCG + L-theanine was mainly divided into four blocks, of which ( 1) and (3) blocks gene expression trend was opposite to that of other treatment groups, and ( 2) and ( 4) blocks gene expression trend were very similar to that of Aβ 25−35 -vs-Aβ 25−35 /EGCG. The expression level of each gene was calculated using the transcripts per kilobase of exon model per million mapped reads (TPM) after normalizing the expression level of each gene.…”
Section: Differentially Expressed Genes Enrichment Analysismentioning
confidence: 93%
“…Proteotoxic stress, mitochondrial dysfunction, and genomic instability lead to cellular hyperactivity and are closely associated with age-related degenerative diseases such as atherosclerosis, type 2 diabetes, osteoporosis, and Alzheimer's disease (1)(2)(3). Under various stressful conditions, cells promote mTOR or other growth factors sensitive growth-stimulating pathways, causing cells to exhibit hyperactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Human MSCs (hMSCs) can be gradually remodeled through cell recombination and arrangement and the regulation of smooth muscle cells by the cytoskeleton ( Parandakh et al, 2017 ). Microtubule actin cross-linking factor 1 (MACF1) is a regulator of cytoskeletal dynamics that is necessary for maintaining bone tissue integrity ( Wang et al, 2021a ), whereas actin in the cytoskeleton is mainly involved in mechanical stress ( Zhou et al, 2018 ). The link between mechanical stimulation, integrin/cytoskeleton/Scr/extracellular signal-regulated protein kinase (ERK) signaling pathway activation, and osteocyte survival provides a mechanical basis for the role of mechanical forces in the bone ( Plotkin et al, 2005 ).…”
Section: Mechanoreceptormentioning
confidence: 99%